MENINGKATKAN KEMAMPUAN PENDIDIKAN BAHASA ARAB MELALUI ANALISA RHOTACISM FONETIS (CADEL) - Zamakhsyari Abdul Majid (STIT Al-Marhalah Al-Ulya Bekasi, 2022)
This paper aims to identify the phenomenon of Phonetic Rhotacism (Cadel) in improving Arabic language skills for children with speech disorders. Phenomenologically, which is related to the learning process, it will greatly affect several factors, one of which is the difficulty of pronouncing some letters properly due to problems with the articulators. This study uses a qualitative-descriptive method by trying to trace various works and writings related to the focus of the study, either directly or indirectly. The works are read carefully and then analyzed and interpreted qualitatively according to the research problems that have been determined previously. There are several disorders that hinder their articulation ability, including distortion, where there is a change in language sounds to sounds that cannot be used, or can change the meaning of the whole word or even have no meaning, this is because the sounds are not recognized in the language. his first language, namely Indonesian, such as the sound ? (qof), ?? ( ta), ?? (za) changed to the sound ? (dad) ?????? ?? ??, ? is changed to sound ?, and also ? (fa) sound is changed to ? (mim) or ? (nun) sound. And all vowel sounds I (kasrah) will be changed to the vowel sound e^. In addition, there is a sound production abnormality called nasality, which is caused by a narrowing or underdevelopment of the nostrils so that air is not expelled properly. Keywords: Phonetic Rhotacism (Cadel), distortion.